Des initiatives locales européennes pour atteindre le facteur 4 ? - Elsa Mor (Développement Durable et Territoires)
In a climate emergency and peak oil context, the local dimension proves to be a strategical scale to take up the challenge of factor 4. It is what we will try to question in this article. We will examine brakes and levers which meet the local initiatives in Europe, in sectoral, energy-climate policies and governance, by leaning of forerunners examples.